1988
DOI: 10.1111/j.1432-1033.1988.tb13870.x
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of the gene encoding the 11‐kDa subunit VIII of the ubiquinol–cytochrome‐c oxidoreductase in Saccharomyces cerevisiae

Abstract: The single nuclear gene encoding the 1 I-kDa subunit VIII of the ubiquinol -cytochrome-c oxidoreductase (complex 111) in Succhuromyces cerevisiae has been inactivated by a one-step gene disruption procedure. Inactivation results in a loss of ubiquinol-cytochrome-c oxidoreductase activity (< 1% wild type) and respiratory deficiency. Cells lacking the 1 I-kDa protein also display lowered steady-state levels of other complex-I11 subunits encoded by nuclear genes including the 14-kDa subunit VII and the Rieske Fe-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
33
1

Year Published

1992
1992
2002
2002

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 27 publications
3
33
1
Order By: Relevance
“…This was also reported for the QCR7' mutant of HR2 [20] where the low amount of cytochrome aa, was thought to be due to the growth of the null-strain on maltose. The fact that such a phenotype is not found in a QCR8' mutant [21] and, more important, in the TNT2 transformant, which is otherwise indistinguishable from the QCR7' mutant, may point to a more causal relation between the N-terminal part of the 14-kDa subunit and the level of cytochrome ua3.…”
Section: Construction Of C-terminal Deletion Mutantsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was also reported for the QCR7' mutant of HR2 [20] where the low amount of cytochrome aa, was thought to be due to the growth of the null-strain on maltose. The fact that such a phenotype is not found in a QCR8' mutant [21] and, more important, in the TNT2 transformant, which is otherwise indistinguishable from the QCR7' mutant, may point to a more causal relation between the N-terminal part of the 14-kDa subunit and the level of cytochrome ua3.…”
Section: Construction Of C-terminal Deletion Mutantsmentioning
confidence: 99%
“…It was shown that the mutant lacked holo-cytochrome b and had severely reduced levels of the Rieske Fe-S protein and the 11-kDa subunit. From the phenotype of this QCR7' mutant and the similar phenotypes of the QCR8" mutant [21] and mutants lacking functional cytochrome b [Sl, it was concluded that the 14-kDa subunit, together with the 11-kDa subunit and cytochrome b, forms a pre-assembly complex which is sensitive to endogenous proteases until association with the protease-resistant subcomplex formed by the two core subunits has taken place. Since this association is prevented in the QCR7', the QCR8' and the cytochrome b mutants, the remainder of the cytochrome b subcomplex is degraded when either of these subunits is missing [22, 231. The pleiotropic effects, caused by the disruption of the QCR7 gene, preclude analysis of the possible mechanistic involvement of this subunit in the activity of the enzyme.…”
mentioning
confidence: 99%
“…A 2478-bp HpaI-SmaI fragment from pUC18 : :M/M23(LEU2) was isolated to transform the mim23 mutants with the LEV2 gene flanked by 5'-noncoding sequences of MIM23. pUCl8 : :MIM23(LEU2) was constructed by cloning a 911-bp PstI fragment of YEpIacl81 ::MIM23 (containing a 1.6-kb SphI fragment harbouring the MIM23 gene [15]) into the PstI site of pUC18 and subsequent insertion of a 1974-bp HpaI-SaZI blunted LEU2 fragment from construct 6 [33] into the blunted SplI site of MIM23, 361-bp upstream of the start codon of MIM23 [15]. were isolated by lysis of the yeast cells with glass beads in breaking buffer and differential centrifugation, as described [36].…”
Section: Methodsmentioning
confidence: 99%
“…6). For example, the absence of the supernumerary subunits Qcr7p or Qcr8p (7,8) leads to a complete respiratory deficiency at any temperature, whereas Qcr6p or Qcr9p appears to be essential only at 36°C (9,10). The precise role of these supernumerary subunits and the nature of the functional interactions existing between them and the catalytic subunits still remain to be elucidated.…”
mentioning
confidence: 99%